2020
DOI: 10.32598/bcn.11.5.352.4
|View full text |Cite
|
Sign up to set email alerts
|

Larger Volume and Different Activation of the Brain in Response to Threat in Military Officers

Abstract: Introduction: Military missions involve stressful and life-threatening situations; however, soldiers should have a healthy cognition on the battlefield despite their high-stress levels. This is an ability that should be gained during prior military training. Successful and influential training is suggested to be associated with structural and functional improvements of the brain. Methods: This study investigated the pattern of brain activation while observing videos relevant to life-threatening situations, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 110 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…Thus, there is no doubt that military training affects positive structural changes in the brain. Moreover, the study showed significantly higher mental toughness of military officers in response to stressful situations compared to the control group [ 15 ]. The above results, combined with the results of our research, unquestionably support the beneficial effect of specialized military training on the EFs of soldiers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is no doubt that military training affects positive structural changes in the brain. Moreover, the study showed significantly higher mental toughness of military officers in response to stressful situations compared to the control group [ 15 ]. The above results, combined with the results of our research, unquestionably support the beneficial effect of specialized military training on the EFs of soldiers.…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors that have been found to have a negative impact on EFs in soldiers is chronic exposure to hypoxia [ 12 ], whilst combat stress has been shown to lead to a deterioration of the processes related to attention and to reduce the activity and integrity of the brain [ 13 ]. On the other hand, military training has been shown to contribute to the ability to maintain control over thoughts and emotions [ 14 ] and to improve overall EFs [ 15 ]. Indeed, physical activity is considered to be the main factor that brings about beneficial and significant improvements in EFs, such as increased information processing, reaction time, and decision-making, as well as improved attention and memory [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data used in this study were from the two previous works (Batouli and Saba, 2020;Batouli et al, 2021). In total, the MRI data from 152 (53F) healthy young individuals were used (in accordance with the number of participants used for building the ICBM152 template).…”
Section: Participantsmentioning
confidence: 99%
“…In comparing the PG volume across studies, the effect of their different methods cannot be excluded (Sigurdardottir et al, 2016). Using atlases for the estimation of regional brain volumes is common (Batouli et al, 2014;Batouli and Saba, 2020), and therefore our PG atlas could be a help to reduce the discrepancies when estimating the PG volume.…”
Section: The Pineal Glandmentioning
confidence: 99%